Do Lifestyle Factors Affect Lower Urinary Tract Symptoms? Results from the Korean Community Health Survey - Kim, Kyu Shik; Jo, Jung Ki; Lee, Ji An; Choi, Bo Youl; Moon, Hong Sang (International neurourology journal, 2019)
To evaluate the relationships between lower urinary tract symptoms (LUTS) and lifestyle factors (physical activity, smoking, alcohol consumption, body mass index, and stress) in Korean men. We analyzed the survey results of South Korean men (n=64,439) who were 40 years of age or older among whom interviews were conducted using questionnaires. Trained interviewers performed face-to-face surveys using computer-assisted personal interviewing, the International Prostate Symptom Score (IPSS), and standard questions. We assessed the relationships of lifestyle factors (physical activity, cigarette smoking, alcohol intake, height, weight, and stress) with LUTS. We observed higher IPSS scores in participants who engaged in no exercise (n=46,008 [71.7%], IPSS=3.19±5.36) than in those who engaged in vigorous physical activity (n=10,657 [17.6%], IPSS=2.28±4.15). Former smokers showed higher total, storage, and voiding symptom IPSS scores than current smokers and nonsmokers. Nondrinkers had higher IPSS scores than current alcohol drinkers. In multivariable logistic regression analysis, we detected no relationship between LUTS and current alcohol drinking in the moderate and severe LUTS groups, using the mild LUTS group as a reference (moderate: 0.91; 95% confidence interval [CI], 0.91-0.91; P<0.001, severe: 0.78; 95% CI, 0.78-0.78; P<0.001). Participants with moderate to severe stress showed higher total IPSS scores than those with no or mild stress (3.38±5.77 vs. 2.88±4.90), with significant relationships between stress and LUTS found in the moderate and severe LUTS groups. In logistic regression analysis, stronger relationships were found for storage and voiding symptoms in the moderate and severe stress groups compared to the mild stress group. A history of smoking, low levels of physical activity, low body mass index, and moderate to severe stress were associated with a greater severity of LUTS. Moderate to severe stress was also related to voiding symptoms. However, there was no association between alcohol intake and LUTS severity.